1993
DOI: 10.1159/000236584
|View full text |Cite
|
Sign up to set email alerts
|

Murine Granulocyte-Macrophage and Mast Cell Colony Formation Promoted by Nerve Growth Factor

Abstract: The nerve growth factor (NGF) is widely distributed in the target tissues of sympathetic neurons. Hemopoietic organs such as the bone marrow (BM) and spleens are known to be innervated by noradrenergic sympathetic neurons. Some of their constitutive cells express NGF receptors (lymphocytes and stroma cells) and its biologic effects have been extensively studied in the immune system and inflammatory responses. However, the effects of NGF on hemopoiesis have been little examined. Recently, we demonstrated that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…NGF has been demonstrated as an important factor for hematopoietic colony growth and differentiation [41]. Previous work documents its ability to directly influence proliferation, differentiation, and maturation of myeloid progenitors along with induction of migration, survival and activation of mature hematopoietic cells [42][43][44]. NGF is also a chemotactic stimulus for human leukocytes and macrophages [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF has been demonstrated as an important factor for hematopoietic colony growth and differentiation [41]. Previous work documents its ability to directly influence proliferation, differentiation, and maturation of myeloid progenitors along with induction of migration, survival and activation of mature hematopoietic cells [42][43][44]. NGF is also a chemotactic stimulus for human leukocytes and macrophages [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…As such, neurotrophins are positioned to regulate the availability of inflammatory cells derived from the marrow, through both direct [41][42][43][44] and indirect mechanisms. Taken together, our data suggest a central role for neurotrophins in the inflammatory process subsequent to infection and identify bone marrow stroma as a novel target for these factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neurotrophic activity, increasing evidences give rise to possible multifunctional properties of NGF on immunocompetent cells including lymphocytes, monocytes/macrophages, and mast cells through functional NGF receptors (4 -11). In prior studies, we have demonstrated that NGF promotes not only granulocyte differentiation from human PBMC and murine bone marrow cells (12,13), but also differentiation of connective tissue-type mast cells from murine bone marrow cells and bone marrow-derived culture mast cells (14). NGF is capable of supporting survival of neutrophils (15), eosinophils (16), and mast cells (9) by preventing apoptosis, and enhancing functional properties of neutrophils, eosinophils, macrophages, and mast cells: phagocytosis, superoxide production, matrix metalloproteinase-9 production, and chemotaxis (11, 12, 16 -20).…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 99%
“…NGF acts as a colony-stimulating factor for human and murine myeloid progenitor cells (83,84). It affects specifically basophilic differentiation (85); induces mediator release from basophils, eosinophils, and neutrophils (80,86,87); acts as a chemoattractant for polytnorphonuclear leukocytes (88,89); and enhances neutrophil phagocytosis (80).…”
Section: Ngf and The Immune Systemmentioning
confidence: 99%